A control‐theoretic approach towards joint admission control and resource allocation of cloud computing services. (23rd March 2015) - Dechouniotis, Dimitrios; Leontiou, Nikolaos; Athanasopoulos, Nikolaos; Christakidis, Athanasios; Denazis, Spyros
Summary Meeting the performance specifications of consolidated web services in a data center is challenging, as the control of the underlying cloud computing infrastructure must meet the service level agreement requirements and satisfy the system's constraints. In this article, we address the admission control and resource allocation problem jointly, by establishing a unified modeling and control framework. Convergence to a desired reference point and stability and feasibility of the control strategy are guaranteed while achieving high performance of the co‐hosted web applications. The efficacy of the proposed approach is illustrated in a real test bed. Copyright © 2015 John Wiley & Sons, Ltd.